Low pathogenicity H5N2 avian influenza outbreak in Japan during the 2005–2006 - Okamatsu, Masatoshi; Saito, Takehiko; Yamamoto, Yu; Mase, Masaji; Tsuduku, Satoko; Nakamura, Kikuyasu; Tsukamoto, Kenji; Yamaguchi, Shigeo (Veterinary microbiology, 2007)
At the end of May 2005, a low-pathogenicity avian influenza (LPAI) virus of subtype H5N2 was isolated for the first time from chickens in Japan. Through active and epidemiological surveillance, 5.78 million chickens on 41 farms were found to be affected and 16 H5N2 viruses were isolated. Antigenic analysis revealed antigenic similarity of these isolates. Phylogenetic analysis showed that they originated from a common ancestor and clustered with the H5N2 strains prevalent in Central America that have been circulating since 1994. Experimental infection of chickens with the index isolate (A/chicken/Ibaraki/1/05) demonstrated that this virus replicated efficiently in the respiratory tract without clinical signs, and dust-borne and/or droplet-borne transmission was considered as a possible mode of transmission. These results suggested that the H5N2 LPAI viruses isolated in Japan were highly adapted to chickens.